Analisis Kinerja dan Efisiensi Alat Uji Nozzle Injector Diesel Berbasis Limbah Hydraulic Jack - Julianro Elvis Sunbanu; Damianus Manesi; Wofrid E Bianome (P3M Politeknik Negeri Jember, 2026)
The limited availability of affordable and reliable diesel nozzle injector testing devices remains a significant constraint in small-scale workshops and mechanical engineering laboratories. In fact, the performance of a nozzle injector plays a critical role in determining fuel atomization quality, which directly affects combustion efficiency and exhaust emissions. This study aims to develop and evaluate the performance of a diesel nozzle injector testing device based on a recycled hydraulic jack as a cost effective and appropriate technology solution. The research employed a Research and Development (R&D) method with an experimental approach, including system design using SketchUp software, prototype fabrication and assembly, and performance testing. Experiments were conducted in five repetitions for each parameter, measuring maximum pressure, pressure stability after 10 seconds (P10s), and spray characteristics in terms of angle and width. The data were analyzed quantitatively using mean, standard deviation, coefficient of variation, as well as efficiency and effectiveness calculations. The results show that the device achieved an average pressure of 257 kg/cm² with a coefficient of variation below 20% and a pressure drop of approximately 7%, which falls within the standard operating range of conventional diesel nozzles (200-300 kg/cm²). The spray pattern exhibited a fan shape with an average angle of 19.67° and a width of 10.4 cm, indicating stable atomization performance. The system efficiency reached 93%, while the effectiveness was 33.3%, suggesting the need for improvement in pressure control.